Análisis, diseño e implementación de una aplicación que sirva de apoyo en el proceso de enseñanza-aprendizaje dirigido a niños especiales - Plata Alarcón, Wendy (2009)
The advance of technology is providing educational alternatives which make the teaching-learning process easier; it involves hardware and software adaptations for disabled people. However, we have to make the right decisions at the moment of including technology in traditional learning environments, of this depends to reduce the probability to give up the computer applications. Based on this argument, in this article are shown the different techniques used for teaching disabled children, for developing a computer application which supports the learning of vowels, numbers, geometric shapes and primary colors, those topics belong to the educational program of children between four and six years old. The computer application design is based on pedagogic models used in Special Education; and, directed by the principles of computer Interaction Machine.